2005
DOI: 10.1248/bpb.28.531
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effects of Irisolidone on tert-Butyl Hyperoxide-Induced Liver Injury

Abstract: To clarify the hepatoprotective effects of kakkalide and its metabolite irisolidone by human fecal microflora, their effects on tert-butyl hydroperoxide (t-BHP)-injured HepG2 cells and mice were investigated. Irisolidone protected HepG2 cells against cytotoxicity induced by t-BHP. However, kakkalide did not protect cytotoxicity. When kakkalide 100 mg/kg was orally administered to mice injured by t-BHP, it significantly inhibited the increase in plasma alanine aminotransferase and aspartate aminotransferase act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…These results suggest that the metabolite, irisolidone, may be the active form for the biological effects of kakkalide, as previously reported, where intraperitoneally and orally administered irisolidone exhibited potent hepatoprotective effects in t-butyl hydroperoxide (BHP)-induced experimental liver injury mice. 14) Even if kakkalide exhibits an antihyperlipidemic effect by the inhibition of HCR, intraperitoneally administered kakkalide, which is a glycoside, may be easily excreted in the urine or bile due to its hydrophilicity compared to that of irisolidone. Kakkalide and irisolidone also significantly lowered the serum TG and TC levels in hyperlipidemic mice induced by long-term feeding of a high fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the metabolite, irisolidone, may be the active form for the biological effects of kakkalide, as previously reported, where intraperitoneally and orally administered irisolidone exhibited potent hepatoprotective effects in t-butyl hydroperoxide (BHP)-induced experimental liver injury mice. 14) Even if kakkalide exhibits an antihyperlipidemic effect by the inhibition of HCR, intraperitoneally administered kakkalide, which is a glycoside, may be easily excreted in the urine or bile due to its hydrophilicity compared to that of irisolidone. Kakkalide and irisolidone also significantly lowered the serum TG and TC levels in hyperlipidemic mice induced by long-term feeding of a high fat diet.…”
Section: Discussionmentioning
confidence: 99%
“…These results support the contention that these isoflavones can act as weak estrogen receptor agonists. Lee et al 7) and Han et al 8) reported that orally administered kakkalide isolated from PF is metabolized by intestinal microflora, and irisolidone might be absorbed into blood. Tectoridin is readily metabolized to tectorigenin by human intestinal bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,13) Preparation of Specimens Fresh fecal specimens from volunteers (male adults in their twenties) (3 g) were septically collected in plastic cups, carefully mixed by a spatula, and suspended with 27 ml of cold saline. The fecal suspension was centrifuged at 100ϫg for 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, we evaluated the hepatoprotective effects of a methanol extract of P. michuacana against paracetamol and carbon tetrachloride (CCl 4 )-induced hepatic damage in albino rats (Perez-Gutierrez & Vargas-Solis, 2009b). The obvious next step for us was to isolate and characterize the flavonoids present in bulb extracts of P. michuacana and to evaluate its protection activity against induced hepatotoxicity, knowing the importance of this strong antioxidants applied in modern liver therapy such as the case of silymarin and catechin (Lee et al, 2005), it was the aim of this investigation to isolate and characterize the flavonoids of P. michuacana by 1D and 2D nuclear magnetic resonance (NMR) experiments proceeding from an antihepatotoxic crude extract. Furthermore, the antihepatotoxic activity of the purified components was tested by antagonization of the CCl 4 intoxication in mice.…”
Section: Research Articlementioning
confidence: 99%